How Are Earnings Managed? An Examination of Specific Accruals* - MARQUARDT, CAROL A.; WIEDMAN, CHRISTINE I. (Contemporary Accounting Research, 2004)
Abstract There is relatively little evidence on the specific accruals used to manage earnings. This paper examines this issue by considering the use of specific accruals in three earnings‐management contexts: equity offerings, management buyouts, and firms avoiding earnings decreases. We argue that the costs of managing earnings through different income statement items vary and that the benefits of earnings management through each of these items depend on the context. We thus make differential predictions regarding which specific accrual will be used to manage earnings in each of the three contexts we consider. To measure earnings management for specific accruals, we develop performance‐matched measures to capture the unexpected component of accounts receivable, inventory, accounts payable, accrued liabilities, depreciation expense, and special items. Consistent with our predictions, we find that firms issuing equity appear to prefer managing earnings upward by accelerating revenue recognition. Specifically, we find that accounts receivable for these firms are unexpectedly high. Conversely, for the management buyout context, we predict and find unexpected accounts receivable to be negative. For firms trying to avoid reporting an earnings decrease, we expect firms to be less concerned with earnings persistence and therefore more likely to use more transitory, and less costly, items to achieve their goal. We find that special items are significantly more positive for this group. This paper provides a further step toward understanding how the incentives behind earnings management affect the method used to achieve earnings goals, and it illustrates the usefulness of examining individual accruals in specific contexts.